SHARIAH BANKING DYNAMICS: FINANCIAL PERFORMANCE AND STABILITY AMID MIDDLE EAST CONFLICT - Putri, Laurina Trisnaning; Sudarmawan, arianto Nurasri (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
Financial system resilience is crucial in maintaining a country's economic stability, and the role of the banking industry, particularly Islamic banks in the Middle East, is a key element in this context. Healthy bank conditions and efficient intermediation operations are vital indicators in determining the level of stability. This study aims to explore the influence of financial performance on the stability of Islamic banks in times of conflict, particularly in the period 2013-2022 in the region. Using quantitative method, this study adopts panel data regression test through Eviews 12 software, with Z-score as the stability measurement tool. Secondary data taken from state financial reports and several public sources form the basis of the analysis, with sample selection using purposive sampling techniques covering 13 countries in the Middle East. The results show that financial performance variables, such as NPF and NPM, have a negative influence on bank stability. In contrast, CAR and ROA variables show a positive influence on bank stability, while CIR and FDR variables have no significant influence on bank stability. The results of this study can serve as a basis for financial supervisory authorities and Islamic banking regulators in the Middle East to consider improvements in managing financial conflict risk. The research also highlights the importance of policy implementation to improve asset quality, risk management, and operational efficiency to strengthen the resilience of Islamic banks in times of conflict.